Ability to Write Advertising Text for Deaf Students Using the Canva Application - Ichlasul Amal; Kamaruddin; Herman Budiono3 (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the ability to write advertisement text for deaf students in class X SMALB Negeri 1 Jambi City using the Canva application. The approach in this research is a quantitative approach and the type of research used in this research is descriptive. Data collection techniques in this study were observation, interviews, and performance tests in the form of writing ad text tests using the Canva application which were carried out by students. Data analysis in this study included assessing student work as assessed by two assessors, namely assessor I (Indonesian teacher), and assessor II (researcher) accompanied by a table to calculate the average student writing results. The results showed that the ability of deaf students in class X SMALB Negeri 1 Jambi City in writing advertisement text using the Canva application could be categorized as very capable, with an average score of 89.6. Evaluation of the elements of the theme gets an average score of 100, which means that students are very capable in developing advertising themes. Elements of advertising content obtain an average value of 84.3, indicating the ability of students to convey capable advertising content. Sentence structure elements obtained an average score of 82.8, indicating that students were able to compose adequate sentences. Evaluation of the spelling element resulted in an average score of 85.7, indicating that students were very capable in terms of spelling. Meanwhile, the appearance element obtained an average value of 95.00, indicating that students were very capable of presenting advertisements with an attractive appearance.